Developing the Agile Institute, an effort to incorporate agile methodologies into Hackensack Meridian Health - El Zein, Lama; Carrillo, Victor A.; Bayly, Robert; Glantz, Erin; Gregg, Bethany; Grove, Mary; Azar, Jose (Frontiers in Public Health, 2025)
The persistent challenge of implementing meaningful and sustainable change in healthcare is well-documented. Barriers include resource limitations, technical insufficiencies, and resistance from entrenched processes and systems within hospitals, clinics, and health systems. Traditional quality improvement (QI) frameworks, while valuable, often fall short in addressing the variability and unpredictability of human behavior and decision-making that reflects the uniqueness of individual experiences and backgrounds working together in a complex organization. In response, Hackensack Meridian Health (HMH), a large integrated health system, established the Agile Institute to promote and diffuse methodologies from Agile Science (sprints, feedback loops, techniques from behavioral psychology to encourage certain behaviors, etc.) as a means to accelerate and sustain quality improvement efforts in care and patient outcomes. This narrative case study describes the conception, structure, and impact of the Agile Institute at HMH. The Institute was designed around three core pillars: training and education, consultation, and organizational identity development. Bootcamps and certification programs equipped staff across the health system with the knowledge and mindset needed to apply Agile. Consultative groups facilitated co-design sessions and iterative sprints, fostering collaboration and interdisciplinary development and implementation of innovative solutions. Intentional brand development helped to build engagement and credibility in both internal and external audiences. Over its first year, the Agile Institute achieved significant milestones: training over 130 staff, launching collaborative physician networks, and supporting system-wide initiatives that improved standardization and patient outcomes. The Institute’s approach-grounded in psychological safety, stakeholder co-design, and iterative feedback-demonstrated the value of embedding Agile principles not only in QI projects but also in organizational culture. Lessons learned highlight the importance of a minimally viable, adaptable structure and the necessity of aligning Agile strategies with both system and individual priorities. The HMH Agile Institute offers a replicable model for other healthcare organizations seeking to drive sustainable, system-wide transformation through Agile.